A Niobium and Nitrogen Co-Doped DLC Film Electrode and Its Electrochemical Properties. Issue 14 (1st January 2017) - Liu, Na; Zhu, Hekang; Wei, Qiuping; Long, Hangyu; Deng, Zejun; Yu, Zhiming; Xie, Youneng; Wang, Jian; Ma, Li; Zhou, Kechao
Abstract : Niobium (Nb) and nitrogen (N) co-doped diamond-like carbon (DLC) film ((Nb:N)-DLC) was fabricated by reactive magnetron sputtering. Atomic force microscopy, Raman spectra and X-ray photoelectron spectroscopy were used to characterize the morphology, microstructure, and composition of the (Nb:N)-DLC film. The (Nb:N)-DLC film has typical DLC characteristics with enlarged and uniform specific surface area. Electrochemical tests show that the proposed co-doped DLC electrode not only presents fast apparent rate constant (1.92 × 10 −2 cm s −1 ), low charge transfer resistance (13.86 Ω cm 2 ), but also possesses excellent electrochemical reversibility and stability in K3 Fe(CN)6 electrolyte. Furthermore, the (Nb:N)-DLC electrode was applied to the determination of dopamine (DA) and an apparent current response to a low concentration of 0.5 μM was obtained by differential pulse voltammetry.